2017
DOI: 10.1016/j.srhc.2016.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Who uses long-acting reversible contraception? Profile of LARC users in the CUPID cohort

Abstract: Reproductive history and reasons for contraceptive use are strong indications of method choice. Promoting LARC as highly effective may not be a sufficient incentive for young women to take up the method when pregnancy prevention may be equal or secondary to their desired non-contraceptive effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
16
2
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 31 publications
(42 reference statements)
4
16
2
1
Order By: Relevance
“…Furthermore, women from rich households were less likely to use LARCs. This is contrary to other studies, which found that household wealth has a positive association with the use, and wealthier women were more likely to use LARCs than poorer women 4 , 23 , 24 .…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Furthermore, women from rich households were less likely to use LARCs. This is contrary to other studies, which found that household wealth has a positive association with the use, and wealthier women were more likely to use LARCs than poorer women 4 , 23 , 24 .…”
Section: Discussioncontrasting
confidence: 99%
“…Women aged 25 years and above were more likely to use LARC methods as compared to women aged 15–24 years. This result is in line with previous studies, which reported that the age of mothers was found to be associated with the use of LARCs because the prevalence of LARC uses increased with age 3 , 4 , 23 , 24 , 26 .…”
Section: Discussionsupporting
confidence: 93%
“…In a study carried out on 3155 participants by Jacqueline Coombes et al, it was found that the history of pregnancy was strongly associated with the increased use of LARC in Australian women (Coombe et al, 2017). A study on the relationship between LARC and parity has also suggested that women who have had one or more children were more likely to use these methods (Cea Soriano et al, 2014).…”
Section: Larc As a Choicementioning
confidence: 99%
“…Although a wide range of LARCs is available in Australia, their uptake has been slow . Between 2004 and 2010, overall contraceptive use among women was reported to be 69%, with intrauterine or implantable LARCs comprising 6.8% .…”
Section: Introductionmentioning
confidence: 99%
“…The relative lack of uptake of LARCs has variously been explained by the attitudes and habits of doctors and women, the upfront costs of LARCs, and the lack of suitable training for LARC insertion . In Australia, it is likely that much can be explained by the popularity of the combined oral contraceptive pill (OC), which is well‐established and subsidised by the Australian government via the Pharmaceutical Benefits Scheme (PBS) . While some LARCs are also funded via the PBS (Mirena® and Implanon®), improving the uptake and use of LARCs more generally is a challenge given barriers to access and the broad experience base with OCs.…”
Section: Introductionmentioning
confidence: 99%